The roles of management commitment and government support on it utilization to achieve organizational performance and competitive advantage - Muafi (2014)
This study investigates SMEs in Yogyakarta –Indonesia about the roles of management commitment and government support on IT utilization to achieve organizational performance and competitive advantage. The respondents were represented by the owners or managers of SMEs.Partial Least Square was used for data analysis.The results show that; (1) there are a significant positive influence of management commitment, indirect government support and direct government support on IT utilization, (2) there is a significant positive influence IT utilization on organizational performance, (3) there is no significant positive influence IT utilization on competitive advantage and (4) there is a significant positive influence competitive advantage on organizational performance.